Combretins A and B, New Cycloartane‐Type Triterpenes from Combretum fragrans. Issue 8 (15th July 2016) - Dawe, Amadou; Kapche, Gilbert Deccaux Wabo Fotso; Bankeu, Jean Jules Kezetas; Fawai, Yakai; Ali, Muhammad Shaiq; Ngadjui, Bonaventure Tchaleu
Abstract : The phytochemical studies on the leaves of the traditionally used medicinal plant Combretum fragrans F.Hoffm (Combretaceae) from Cameroon have led to the isolation of combretins A and B (1 and2, resp.), two new cycloartane‐type triterpenes from the AcOEt‐soluble subfraction along with β ‐sitosterol (3 ), oleanolic acid (4 ), ursolic acid (5 ), and pratensein (6 ). The compounds4 – 6 are reported for the first time from this species. The structures of the new triterpenes were elucidated by spectroscopic techniques including 1 H‐ and 13 C‐NMR (DEPT), and 2D‐NMR experiments. Abstract :